ETHIC NORMS OF WORKING WITH SOURCES - Makharadze, Ia (European Scientific Journal, ESJ, 2012)
The goal of this article is to clarify the definition of moral and ethic standards of self-regulation of journalistic activities in the media through theoretical grounding of the concept coupled with examples of its applications in practical journalism. By achieving a more comprehensive understanding of what â€œJournalistic self-regulationâ€ and â€œPress self-regulationâ€ mean in the field of media, one becomes better equipped to formulate professional ethics that is effective and holds the potential to understanding ethic standards and problems of human activities in the modern information space. Its aim is to study fundamental human rights and obligations on gaining and transferring the information, the main forms, mechanisms and directions of ethic control on information. The media service ethic code clearly formulates journalistsâ€™ obligations, permissions and prohibitions.